The coffee paradox: Global markets, commodity trade and the elusive promise of development - Daviron, Benoit; Ponte, Stefano (CTA / Zed Books, 2005)
The focus of this book is on the global coffee trade, highlighting the difficulties and opportunities of the trade for poor coffee-growing nations. It covers commodity chains, labour, regulations and governance, quality control, consumer issues, transparency, sustainable coffee initiatives and business- and donor-oriented approaches.